Penggunaan Media Audio-Taktil dalam Pembelajaran IPA bagi Siswa Tunanetra di Kelas Inklusi - Sherly Sofiana; Suaibatul Aslamiah; Sri Rodiatul Amini (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
The development of adaptive and multisensorial learning media is a critical aspect in supporting the success of inclusive education, particularly for visually impaired students who face challenges in comprehending abstract concepts in science subjects. These limitations necessitate innovative learning media capable of optimizing information processing through alternative sensory modalities, namely auditory and tactile. Audio-tactile media represents an innovation that simultaneously integrates sound and touch stimulation to facilitate multisensorial conceptual understanding and enhance the cognitive construction of visually impaired students. This study employs a qualitative descriptive approach utilizing observation, in-depth interviews, and documentation techniques to evaluate the effectiveness of audio-tactile media in the context of science learning within inclusive classrooms. The results indicate that audio-tactile media significantly improves conceptual understanding, learning motivation, and active participation among visually impaired students. Additionally, this media strengthens social interaction among students and supports teachers in delivering material inclusively and responsively to individual learner needs. The novelty of this research lies in the application of learning media that combines two sensory modalities as an innovative pedagogical strategy to overcome cognitive barriers caused by visual impairment, while simultaneously enriching the multisensorial learning experience. These findings contribute significantly to the development of an adaptive, inclusive, and equitable science learning model for students with special needs. Accordingly, audio-tactile media is recommended as an effective alternative to create an inclusive and high-quality learning environment.